2014
DOI: 10.4172/2332-2632.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Rotational Features – Preliminary Investigations

Abstract: During the experiments bubbles were generated in natural sea water or in artificial sea water by the effervescence method using a small (c. 1/10 of Salt Ems factitium (SEf) pill; by adding a small amount of sea salt or by adding 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Experiments on the rotational features of a rising bubble (Marks, 2014) suggest that interaction with ions in "clean or relatively clean" sea water can separate cations and anions into charge polarized and oppositely rotating domains. The principle on which ions are separated by rising bubbles is based on mass differences between the main ionic hydrates (Cland Na + ) that compose sea water.…”
Section: Rising Bubblesmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments on the rotational features of a rising bubble (Marks, 2014) suggest that interaction with ions in "clean or relatively clean" sea water can separate cations and anions into charge polarized and oppositely rotating domains. The principle on which ions are separated by rising bubbles is based on mass differences between the main ionic hydrates (Cland Na + ) that compose sea water.…”
Section: Rising Bubblesmentioning
confidence: 99%
“…Using a Cl/Na atomic mass equal to 1.542 (Kropman and Bakker, 2001) the bubble mediated selection of ions that collide with bubble outer curvatures may be based on ionic hydrate mass differences. Anionic hydrates are more resistant to displacement and concentrate on the upper bubble half sphere, while lighter and smaller cationic hydrates are drawn to a low pressure area, associated with the bubble bottom half sphere and sub-bubble vortex (Marks, 2014;2015). Ionic motion accelerated at the moment of Ocean Sci.…”
Section: Rising Bubblesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been indicated that these microorganisms may cause gastrointestinal disturbances, airways disorders and skin allergies [9][10][11][12][13]. Since microorganisms which are present in the seawater may be easily transferred into the atmospheric air, it is important to monitor the sanitary and epidemiological conditions of the seawater and coastal air [6,14]. Thus, the supervision over the disposal of treated sewage into the gulf of gdansk (among others from the two largest sewage treatment plants in Poland) has become a necessity.…”
Section: Introductionmentioning
confidence: 99%